Imidacloprid Resistance Challenges in Brazilian Strains of Drosophila suzukii (Diptera: Drosophilidae) - Felipe Andreazza; Flávio Roberto Mello Garcia; Pedro Bento da Silva; Lucas Bretas Barbosa; Joel Marques de Oliveira; Gabriel Netto Araújo; Eugenio E. Oliveira (Insects)
Drosophila suzukii (Matsumura) is a relevant pest affecting berries and stone fruits globally, including in the Neotropical region, where its invasion was reported about a decade ago. Despite chemical control being the main management method for D. suzukii, data on insecticide susceptibility in Neotropical D. suzukii populations are scarce. Here, we assessed the susceptibility of three field-collected Brazilian D. suzukii populations to four insecticides (i.e., deltamethrin, permethrin, spinetoram, imidacloprid) and contrasted this with a standard insecticide-susceptible population. Using the discriminating concentration (LC90) from the standard susceptible population, we identified resistant populations. Synergist exposure (piperonyl butoxide, triphenyl phosphate, diethyl maleate) indicated the role of detoxification enzymes in resistance. Our results showed that deltamethrin was the most toxic, followed by spinetoram, permethrin, and imidacloprid. While all field populations were similarly susceptible to pyrethroids and spinosyns, one population from Minas Gerais (i.e., Paula Candido) had significantly lower imidacloprid susceptibility, with only 53.4 ± 5.2% mortality at 10.0 g/L (the equivalent of 10-fold the estimated imidacloprid LC90). Only piperonyl butoxide increased the imidacloprid susceptibility of Paula Candido flies. Our findings indicate the occurrence of cytochrome P450 enzyme-based imidacloprid resistance in the state of Minas Gerais, which can challenge the management of D. suzukii in Brazil.